Website to promote the formation of values in students of the Labor Education career (REDEL. Revista Granmense de Desarrollo Local, 2025)
The subject of values has been extensively investigated from different sciences and areas of knowledge. This article deals with the application of informatics for the formation of civic values in higher education students. It aimed to propose a website that promotes the formation of these values in third-year students of the Bachelor’s degree in Labor Education at Granma University. Several research methods were used: at the theoretical level, inductive-deductive and analytical-synthetic; at the empirical level, observation, survey, interview and documentary analysis; in the statistical-mathematical, descriptive statistics. All allowed the website design and data processing necessary for research. The computer product provided favored work with the formation of citizen values in third-year students of the Bachelor’s degree in Labor Education from Granma University.
Keywords: Citizen Education; formation of values; website; Labor Education.